A review of the genus Spilomena Shuckard (Hymenoptera: Crabronidae) with the description of six new species from India - Rajan, Tessy; Kumar, P. Girish; Sureshan, P. M.; Binoy, C. (Zootaxa, 2021)
The Indian species of Spilomena Shuckard are reviewed resulting in the description of six new species viz., S. attenboroughi Tessy, Sureshan et Binoy, S. fulvopleuris Tessy, Sureshan et Binoy, S. reticularis Tessy, Sureshan et Binoy, S. sahyadriensis Tessy, Sureshan et Girish Kumar, S. tsunekii Tessy, Sureshan et Girish Kumar, and S. tuberculata Tessy, Sureshan et Girish Kumar, all from Southern India. A key to Indian species of Spilomena is provided.